2023
DOI: 10.19045/bspab.2023.120121
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the pharmacological potential of Trametes hirsuta (White Rot Fungi): Analgesic, anti-Inflammatory, antispasmodic and antimicrobial activities

Abstract: A healthy and well-balanced diet is essential for illness prevention, especially when it comes to oxidative stress. Mushrooms have been utilized in oriental medication for centuries to prevent and treat a variety of diseases. Mushroom extracts are increasingly available as dietary supplements, especially to increase immune function. In current study, the pharmacological potential of Trametes hirsuta was investigated, specifically its analgesic, anti-inflammatory, and antispasmodic activity, as well as its anti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 11 publications
(11 reference statements)
0
2
0
Order By: Relevance
“…GC-MS analysis of T. polyzona methanolic extracts showed the following 14 bioactive compounds: caprylic acid methyl ester, tridecanoic acid methyl ester, myristoleic acid methyl ester, cis-10 pentadecanoic acid methyl ester, palmitoleic acid methyl ester, heptadecanoic acid methyl ester, stearic acid methyl ester, elaidic acid methyl ester, oleic acid methyl ester, linolelaidic acid methyl ester, g-linoleic acid methyl ester, x-linolenic acid methyl ester, heneicosanoic acid methyl ester, and cis-11-14-eicosadienoic acid methyl ester. Recently, Begum et al (2023) reported that the aqueous extracts of T. hirsuta exhibited antimicrobial activity against S. aureus (DIZ 16.00 ± 0.66 mm for 20 mg/mL extract), K. pneumonia (DIZ 14.66 ± 0.88 mm for 20 mg/mL extract) and Salmonella enterica (DIZ 13.00 ± 0.88 mm for 20 mg/mL extract). They also related that ethanolic extracts of T. hirsuta had significant analgesic, anti-inflammatory and antispasmodic activities.…”
Section: Biologically Active Secondary Metabolites Produced By White-...mentioning
confidence: 99%
“…GC-MS analysis of T. polyzona methanolic extracts showed the following 14 bioactive compounds: caprylic acid methyl ester, tridecanoic acid methyl ester, myristoleic acid methyl ester, cis-10 pentadecanoic acid methyl ester, palmitoleic acid methyl ester, heptadecanoic acid methyl ester, stearic acid methyl ester, elaidic acid methyl ester, oleic acid methyl ester, linolelaidic acid methyl ester, g-linoleic acid methyl ester, x-linolenic acid methyl ester, heneicosanoic acid methyl ester, and cis-11-14-eicosadienoic acid methyl ester. Recently, Begum et al (2023) reported that the aqueous extracts of T. hirsuta exhibited antimicrobial activity against S. aureus (DIZ 16.00 ± 0.66 mm for 20 mg/mL extract), K. pneumonia (DIZ 14.66 ± 0.88 mm for 20 mg/mL extract) and Salmonella enterica (DIZ 13.00 ± 0.88 mm for 20 mg/mL extract). They also related that ethanolic extracts of T. hirsuta had significant analgesic, anti-inflammatory and antispasmodic activities.…”
Section: Biologically Active Secondary Metabolites Produced By White-...mentioning
confidence: 99%
“…Natural chemicals obtained from mushrooms can be thoroughly investigated and evaluated, which can be extremely beneficial for treating both infectious and noninfectious disorders [ 7 , 8 ]. Medicinal mushrooms and fungi are believed to have 130 different therapeutic properties, including antiallergic [ 9 ], antiarthritic, antiasthmatic [ 10 ], anticancer [ 11 ], pesticide [ 12 ], antidepressive [ 13 ], antidermatophytic [ 14 ], antidiabetic [ 15 ], antifertility, antifungal [ 15 ], antihelminthic [ 16 ], cytotoxic [ 17 ], antihypercholesterolemic [ 18 ], antihyperlipidemic [ 19 ], antihypertensive [ 20 ], antihypocholesterolemic [ 21 ], anti-inflammatory [ 15 ], antimalarial [ 22 ], antimicrobial [ 15 ], antioxidant [ 11 ], antiparasitic [ 23 ], antispasmodic [ 24 ], antiviral [ 13 ], anticardiovascular illnesses [ 18 ], hepatoprotective [ 10 ], immunomodulator [ 22 ], immunostimulant [ 13 ], insecticidal [ 22 ], larvicidal [ 25 ], nematicide [ 26 ], nephroprotective, neuroprotective [ 13 ], osteoprotective [ 4 ], and vasodilator [ 27 ], among others.…”
Section: Introductionmentioning
confidence: 99%